The effect of the interruption of agitation, temporary cooling, and pneumatic tube transportation on platelet quality during storage for transfusion - Böhmert, Stephanie; Kübel, Sarah; Müller, Markus Matthias; Weber, Christian Friedrich; Adam, Elisabeth; Dröse, Stefan; Zacharowski, Kai; Fischer, Dania (Transfusion, 2021)
Background Conditions during blood product storage and transportation should maintain quality. The aim of this in vitro study was to investigate the effect of interruption of agitation, temporary cooling (TC), and pneumatic tube system transportation (PTST) on the aggregation ability (AA) and mitochondrial function (MF) of platelet concentrates (PC). Study Design and Methods A PC was divided equally into four subunits and then allocated to four test groups. The control group (I) was stored as recommended (continuous agitation, 22 ± 2°C) for 4 days. The test groups were stored without agitation (II), stored as recommended, albeit 4°C for 60 minutes on day (d)2 (III) and PTST (IV). Aggregometry was measured using Multiplate (RocheAG; ADPtest, ASPItest, TRAPtest, COLtest) and MF using Oxygraph-2k (Oroboros Instruments). The basal and maximum mitochondrial respiratory rate (MMRR) were determined. AA and MF were measured daily in I and II and AA in III and IV on d2 after TC/PTST. Statistical analysis was performed using tests for matched observations. Results Eleven PCs were used. TRAP-6 induced AA was significantly lower in II when compared to I on d4 (P = 0.015*). In III the ASPItest was significantly lower (P = 0.032*). IV showed no significant differences. The basal and MMRR were significantly reduced over 4 days in I and II (for both rates in both groups: P = <0.0001*). No significant differences occurred on d4 (P = 0.495). Conclusion Our results indicate that ex vivo AA and MF of PCs are unaffected, even in no-ideal storage and transport circumstances with respect to agitation, temperature, and force.